NVTIA Four-Component Synovitis Therapeutic Composition for Cartilage Tissue Repair: Formulation Architecture, Preclinical Signals, and Published Translational Evidence - Yassine, Jabar; Semenza, Gregg L.; Brooks, Hailey (International Journal of Public Health and Medical Research, 2026)
This template explains and demonstrates how to prepare your camera-ready paper for Warwick Evans Publishing. The best is to read these instructions and follow the outline of this text. Please make the page settings of your word processor to A4 format (21 x 29.7 cm); with the margins: bottom 1.9 cm (0.74 in) and top 2.5 cm (0.98 in), right/left margins must be 2 cm (0.78 in). All manuscripts must be in English, also the table and figure texts, otherwise, we cannot publish your paper. All manuscripts must be in English, also the table and figure texts, otherwise, we cannot publish your paper.